Second Nature and Illusion in the Young Th. W. Adorno: Programmatic Notes on “The Idea of Natural History” - Montero Salas, Osvaldo (2024)
This article delves into Adorno’s early text, “The Idea of Natural History”,which can be seen as a precursor to a research proto-program focused onthe problem of illusion. From the theoretical, methodological, and normativeframework of critical theory, this article’s hypothesis holds that Adorno’s earlytext provides essential resources for understanding his intellectual projectas a sophisticated theory of illusion capable of uncovering the structuresunderlying the apparent forms of modern reality. The article begins byexamining the context in which the text was developed and then analyzes theinfluence of Lukács and Benjamin on Adorno’s concept of second nature. Itthen discusses illusion as an “authentic problem of natural-history” and tracesthe presence of this theme throughout Adorno’s work, suggesting that it couldbe interpreted as a critical theory of illusion. Finally, the article emphasizesthe relevance of this underlying theme for understanding Adorno’s theoreticalproposal, especially in a contemporary context where deciphering illusionis crucial for understanding the multiple dimensions and challenges of oursocieties.